Coordination and transactions are key to building an operational SOA secrets of SOA design. - Linthicum, David
Building an SOA usually means leveraging a loosely coupled-type architecture. While the benefits of a loosely coupled SOA with many services are apparent, the operational characteristics can be a nightmare. However, with a bit of planning and the use of some standards, your SOA will be both reliable and functional.